Bibliometric Analysis of Global Research Trends on the Antidiabetic Potential of Andaliman (Zanthoxylum armatum DC.) - Rosyid Ridho, Muhammad Ainur; Indriani, Ratri Dwi; Hidayanti, Restu (LPPM Universitas Dhyana Pura, 2025)
This study presents a bibliometric analysis of global research trends concerning the antidiabetic potential of Zanthoxylum armatum DC. Data were retrieved from the Scopus database and analyzed using VOSviewer to map keywords, thematic clusters, and research evolution. The findings highlight a strong focus on antidiabetic effects and the pharmacological activity of bioactive compounds such as alkylamides, flavonoids, and phenolics, which act through mechanisms including inhibition of α-glucosidase and α-amylase, activation of the AMPK pathway, and enhancement of glucose transport. The visualizations also reveal the incorporation of Z. armatum into low-glycemic functional foods. This study underscores the plant’s promising role in natural diabetes therapy and the value of bibliometric approaches in systematically evaluating research landscapes.